2009
DOI: 10.1128/jb.00251-09
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Plasticity, and Evolution of the vpma Gene Family, a Genetic System Devoted to High-Frequency Surface Variation in Mycoplasma agalactiae

Abstract: Mycoplasma agalactiae, an important pathogen of small ruminants, exhibits a very versatile surface architecture by switching multiple, related lipoproteins (Vpmas) on and off. In the type strain, PG2, Vpma phase variation is generated by a cluster of six vpma genes that undergo frequent DNA rearrangements via sitespecific recombination. To further comprehend the degree of diversity that can be generated at the M. agalactiae surface, the vpma gene repertoire of a field strain, 5632, was analyzed and shown to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
3
26
0
2
Order By: Relevance
“…Remarkably, whole-genome sequence analysis has revealed that extensive horizontal gene transfer (HGT) events, affecting up to 18% of the M. agalactiae genome, occurred between M. agalactiae and members of the mycoides cluster, illustrating the unexpected plasticity and adaptability of the mycoplasma genome (44,45). Recent advances in whole-genome sequencing have greatly facilitated the study of mycoplasmas (2,33,34,44,45). Unfortunately, these data alone have been of little help in identifying the mechanism underlying diseases caused by mycoplasmas.…”
mentioning
confidence: 99%
“…Remarkably, whole-genome sequence analysis has revealed that extensive horizontal gene transfer (HGT) events, affecting up to 18% of the M. agalactiae genome, occurred between M. agalactiae and members of the mycoides cluster, illustrating the unexpected plasticity and adaptability of the mycoplasma genome (44,45). Recent advances in whole-genome sequencing have greatly facilitated the study of mycoplasmas (2,33,34,44,45). Unfortunately, these data alone have been of little help in identifying the mechanism underlying diseases caused by mycoplasmas.…”
mentioning
confidence: 99%
“…In MA, the vpma locus has been thoroughly studied and shown to encode genes with related sequences [15,21-23]. The size of the vpma repertoire (number of vpma genes) varies between strains, but is constant within each strain.…”
Section: Resultsmentioning
confidence: 99%
“…P30, P48, P55 and P80 are surface proteins of Mycoplasma agalactiae, but P40 is the immunodominant protein and suitable for diagnostic assays like ELISA, as a sensitive assay for detection of host serum antibodies against Mycoplasma agalactiae (Nouvel, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Many surface lipoproteins including P30, P40, P80, P55, Vpma, P48, etc. which have been found in Mycoplasma agalactiae, are able to switch their gene expression during immune evasion and adherence to epithelium cells underc host physiologic conditions (Nouvel, 2009). Genomic and proteomic analyses have provided powerful immunological insights into a few proteins of this pathogen (including P40, Vpma and P48) as suitable agents for determination kits or detection reports.…”
Section: Introductionmentioning
confidence: 99%